2014
DOI: 10.1177/0004867414525840
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and psychosocial outcomes to age 30: A fixed-effects regression analysis

Abstract: The findings of this study suggest that exposure to unemployment had small but pervasive effects on psychosocial adjustment in adolescence and young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 45 publications
1
33
1
1
Order By: Relevance
“…The table shows that there was a statistically significant (p \ 0.001) main effect of gender for three life event domains: interpersonal problems, illness/death, pregnancy/parenthood; and combined across all domains. These analyses showed that women rated their experience of the 25), suggesting that the observed gender differences in reported distress did not vary with age at assessment. The regression models for the life event domains showing significant associations with gender in Table 2 were extended, in a sequential process, to adjust for mediation by (1) child/adolescent factors and (2) adult mental health and self-esteem (see ''Methods'').…”
Section: Sample Size and Sample Biasmentioning
confidence: 82%
See 3 more Smart Citations
“…The table shows that there was a statistically significant (p \ 0.001) main effect of gender for three life event domains: interpersonal problems, illness/death, pregnancy/parenthood; and combined across all domains. These analyses showed that women rated their experience of the 25), suggesting that the observed gender differences in reported distress did not vary with age at assessment. The regression models for the life event domains showing significant associations with gender in Table 2 were extended, in a sequential process, to adjust for mediation by (1) child/adolescent factors and (2) adult mental health and self-esteem (see ''Methods'').…”
Section: Sample Size and Sample Biasmentioning
confidence: 82%
“…However, examination of gender by age interactions revealed no statistically significant interactions (all p values p [ 0. 25), suggesting that gender differences in the rate of life event reporting did not vary across ages of assessment. Table 2 shows the associations between gender and mean (SD) distress per life event reported at each age and pooled across observations at 30 and 35 years.…”
Section: Sample Size and Sample Biasmentioning
confidence: 94%
See 2 more Smart Citations
“…To our knowledge, no study investigated longitudinal associations between NEET youth with risky behaviors and mental health, although this design is required for the examination of causality and reverse causality [11]. This study aimed to fill in this gap within a sample of young Swiss men.…”
mentioning
confidence: 99%